2016
DOI: 10.1111/tri.12833
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety of high-dose, sucrose-free intravenous immunoglobulin in kidney transplant recipients: an observational study

Abstract: High-dose intravenous immunoglobulin (IVIg) is commonly used during kidney transplantation. Its nephrotoxicity has been attributed to sucrose stabilizers. We evaluated the renal safety of newer formulations of sucrose-free IVIg. We retrospectively studied clinical and histological data from 75 kidney recipients receiving high-dose, sucrose-free IVIg courses. This group was compared with 75 matched kidney recipients not treated with IVIg. Sucrose-free IVIg treatment was not associated with any acute kidney inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Taken together, our data (clinical and experimental) suggested that the benefits of high dose IVIG after kidney transplantation are limited. Furthermore, high dose IVIG have been associated with more tubular macrovacuoles and chronic tubulointerstitial changes after kidney transplantation (35,36). Our results remain to be confirmed in a larger population which could lead to deep modifications of the current use of high dose IVIG in clinical practice after kidney transplantation.…”
Section: Discussionmentioning
confidence: 66%
“…Taken together, our data (clinical and experimental) suggested that the benefits of high dose IVIG after kidney transplantation are limited. Furthermore, high dose IVIG have been associated with more tubular macrovacuoles and chronic tubulointerstitial changes after kidney transplantation (35,36). Our results remain to be confirmed in a larger population which could lead to deep modifications of the current use of high dose IVIG in clinical practice after kidney transplantation.…”
Section: Discussionmentioning
confidence: 66%
“…Sucrose-free IVIG formulations have been used safely without adverse renal side effects in patients with renal compromise. 315,316 Summary of previously published literature: Nephrotic syndrome Special considerations for nephrotic patients with SHG include the contribution of BCTT and the difficulty of adequate repletion due to urinary protein loss when IgG-RT is deemed necessary. The contribution of SHG in infectious complications of nephrotic syndrome remains unclear.…”
Section: Protein-losing Conditions Nephrotic Syndromementioning
confidence: 99%
“…À partir de 2010, l'utilisation des IgIV sans saccharose a été répandue en vue Celles-ci sont associées à une fibrose interstitielle et à une moins bonne fonction rénale à un an dans une des études [45]. La qualité du greffon (âge du donneur et fibrose interstitielle initiale) semble être un des facteurs favorisant la susceptibilité rénale aux IgIV [45,46]. La seconde étude suggère que les IgIV sans excipient glucidique seraient moins associées à ces lésions tubulaires [46].…”
Section: Effets Indésirables Des Igiv Et Risque De Néphrotoxicitéunclassified
“…La qualité du greffon (âge du donneur et fibrose interstitielle initiale) semble être un des facteurs favorisant la susceptibilité rénale aux IgIV [45,46]. La seconde étude suggère que les IgIV sans excipient glucidique seraient moins associées à ces lésions tubulaires [46]. Il est à noter que l'on manque de données pour évaluer la toxicité tubulaire des perfusions d'IgIV au long cours et leurs conséquences sur la fibrogenèse et le déclin de la fonction rénale.…”
Section: Effets Indésirables Des Igiv Et Risque De Néphrotoxicitéunclassified